Rancang Bangun Sistem Absensi Pelajar PKL dan Karyawan Berbasis QR Code, Selfie, dan Validasi Lokasi pada Omaira Fas Internet - Haris Usman; Farizi Ilham; Muhamad Hariri Fadilah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Omaira Fas Internet is an Internet service provider (ISP) based on the RT/RW Net WiFi network that specializes in network installation, network maintenance, and customer service. In addition to its full-time staff, the company regularly hosts a significant number of students participating in Field Work Practice (PKL) programs from various vocational schools, with the number sometimes reaching dozens of students during certain periods. Currently, the attendance process at Omaira Fas Internet is still done manually by sending photos to a WhatsApp group as proof of attendance. This process poses several challenges, such as attendance data that is not systematically organized, the difficulty of compiling attendance records, and suboptimal supervision of PKL students. The objective of this internship is to design and develop a web-based attendance system that can assist the company in managing employee and PKL student attendance data more effectively and accurately. The methods used in preparing this report include observation, interviews, and literature review, while the system development method employs the Waterfall model. The developed system features QR code scanning, selfies for attendance validation, office location radius validation, check-in and check-out attendance, leave and sick leave, automatic attendance summaries, user data management, WhatsApp notifications to parents and supervising teachers, as well as report export to Excel and PDF formats. The expected outcome of this system is the creation of a more effective, accurate, and structured attendance process, as well as simplifying the task of managing and reporting attendance data for interns and employees for company administrators.